Searching for Sycorax : black women's hauntings of contemporary horror - Brooks, Kinitra Dechaun (Rutgers University Press, 2018)
Searching for Sycorax highlights the unique position of Black women in horror as both characters and creators. Kinitra D. Brooks creates a racially gendered critical analysis of African diasporic women, challenging the horror genre's historic themes and interrogating forms of literature that have often been ignored by Black feminist theory. Brooks examines the works of women across the African diaspora, from Haiti, Trinidad, and Jamaica, to England and the United States, looking at new and canonized horror texts by Nalo Hopkinson, NK Jemisin, Gloria Naylor, and Chesya Burke. These Black women fiction writers take advantage of horror's ability to highlight U.S. white dominant cultural anxieties by using Africana folklore to revise horror's semiotics within their own imaginary. Ultimately, Brooks compares the legacy of Shakespeare's Sycorax (of The Tempest) to Black women writers themselves, who, deprived of mainstream access to self-articulation, nevertheless influence the trajectory of horror criticism by forcing the genre to de-centralize whiteness and maleness.